(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2019)
In the spring of 2019, PEML organized, together with the Italianistic class of the Ambrosiana Academy, a series of seminars that has the title: “Stesure, redazioni, revisioni, riscritture” ("Drafting, editing, revising, rewriting"). The starting point of this proposal arises from a question: is there a difference between "stesura" and "redazione", often used as synonyms in the Italian philology and critical pages?If there is a difference, what is the specificity of both? What definitions can therefore be given? When can we use the term "revisione" and when do we begin to use the word "riscrittura"? How does a work change by changing its index? Attempting to answer the above questions means both reflecting on a possible common glossary, and dealing with the individual cases that the history of literature or critics continually presents to scholars. The section "Open Conferences" of this number 4/II (2019), therefore, offers some reports of the speeches which were held in the months of September, October and November 2019. The first of these is “Foscolo and the translation of Sterne’s "Sentimental Journey": the unpublished editorial of 1812”, by Giulia Ravera.